Alphabet ice cream - Heap, Sue; Sharratt, Nick (London : Puffin Books, 2014)
This very simple text is about two friends, Sue and Nick, who like very different things but are still best friends. They take us through all their favourite things from A to Z. The text is perfect for children learning to read.
"An A-Z of alphabet fun."--Cover.
Keywords: English language -- Alphabet -- Pictorial works -- Juvenile literature